Penerapan Sikap Kerja Seiri, Seiton, Seiso, Seiketsu, Shitsuke (5S) Melalui Pelatihan Gemba Kaizen - Ardiansyah Jasman (CV. Syntax Corporation Indonesia, 2021)
The application ofwork is one of the indicators of success and successof a company inachieving its goals. Gemba kaizen is a Japanese working culture that is used to make continuous or continuous improvements and improvements in a workplace (Fitri, 2016) The purpose of this study is to find out the difference in work attitudes (5S) before and after being given Gemba Kaizen training. This study is a quantitative study with an experimental approach concluded that there is a difference in 5S work attitudes in subjects between before (pretest) and after (posttest) given Gemba Kaizen training. This is seen based on the results of significance showing a p-value of 0.002, where if the p-value is less than 0.05 then the hypothesis is declared acceptable. This means that by providing Gemba Kaizen Training the application of 5S work attitudes can be formed or appeared on a particular subject